ANALISIS SANKSI HUKUM ATAS PERTANGGUNGJAWABAN PEMERINTAH TERHADAP INSIDEN BOCORNYA DATA PRIBADI MASYARAKAT DARI PUSAT DATA NASIONAL (PDN) INDONESIA - Anak Agung Putu Wiwik Sugiantari; I Wayan Gde Wiryawan; I Gusti Bagus Hengki; Ni Nyoman Manik Gita Asrita; I Kadek Agus Aditya Putra (Faculty of Law, Mahasaraswati University, Denpasar, 2024)
The concept of legal responsibility is related to legal obligations, which means that a person is legally responsible for their actions and can be subject to sanctions if their actions conflict with their obligations. The term governmental liability is a form of accountability resulting from government actions that violate the law. One of the things that the government must be held accountable for is the failure to protect the personal data of Indonesian citizens in the incident where the National Data Center was breached due to a weak national defense system. This research discusses legal sanctions that can be applied to the government and the implications of these sanctions in the world of law in Indonesia. The methodology that researchers use is a normative legal research methodology with a statutory and regulatory approach, where the results are presented using analytical descriptive techniques. The aim of this research is to find new legal facts in the field of data protection. It can be concluded that the sanctions imposed within the scope of government office responsibilities for failure to protect personal data are in the form of administrative sanctions or civil sanctions, while from the perspective of personal responsibility they can be in the form of administrative sanctions or civil or criminal sanctions. The existence of legal sanctions for protecting personal data (UU PDP, UU ITE) has created a definite legal atmosphere, but these regulations have not been effective in preventing the onslaught of various types of multi-diverse risks in the cyber world